Influence of Green Marketing Strategy and Brand Image on Purchase Decision with Mediation of Purchase Intention (Case Study on Healthy Food Products Matoh Cassava Chips in Bojonegoro Regency) - Istikhomah; Budi Setiawan; Fitria Dina Riana (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to describe the application and influence of Green marketing strategy and Brand image on purchase decision through purchase intention and the right strategy for marketing Matoh Cassava Chips. The method used is quantitative with a sample of 80 consumers of Matoh Cassava Chips in Bojonegoro Regency, the sample is determined by accidental sampling, data obtained using a questionnaire. The data analysis technique in this study uses descriptive analysis and Structural Equation Modeling - Partial Least Square (SEM-PLS) analysis to test the hypothesis and determine the influence between variables. The results of the analysis show that the implementation of green marketing strategies and overall brand image has a high category, there is a significant influence of exogenous variables on purchasing decisions, purchase intention significantly mediates the influence of both on purchasing decisions, and makes marketing strategies that combine these two factors an effective approach in influencing consumer behaviour. So from these results it can be concluded that Green marketing strategy and Brand image have a significant effect on purchase decisions, as well as purchase intention which is able to significantly mediate this influence.